1995
DOI: 10.1007/bf02246158
|View full text |Cite
|
Sign up to set email alerts
|

Urges to smoke during the first month of abstinence: relationship to relapse and predictors

Abstract: The urges to smoke reported by 215 former smokers were measured 1 day, 7 days, 14 days and 30 days after they quit to examine: (a) the time course of smoking urges, (b) the relationship of urges to relapse, and (c) predictors of urges to smoke. Urges to smoke were strongest 1 day after quitting, and decreased at each subsequent measurement point. Urges were a powerful predictor of relapse. At each of the four assessment points, abstinent subjects who reported stronger urges to smoke were more likely to relapse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
135
3
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(148 citation statements)
references
References 31 publications
8
135
3
2
Order By: Relevance
“…Thus, despite serious cutting down, the smoking rate still predicted abstinence. Urges to smoke have not been tested previously as a predictor of smoking cessation during pregnancy, and in this study frequency of urges to smoke showed significant results at the two times and the combined score for urges was also significant at end‐of‐pregnancy, which is consistent with the results for studies in non‐pregnant populations 37, 40, 41.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thus, despite serious cutting down, the smoking rate still predicted abstinence. Urges to smoke have not been tested previously as a predictor of smoking cessation during pregnancy, and in this study frequency of urges to smoke showed significant results at the two times and the combined score for urges was also significant at end‐of‐pregnancy, which is consistent with the results for studies in non‐pregnant populations 37, 40, 41.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we also examined the HSI and non‐HSI (comprised of the other four items in the FTCD) as predictors of abstinence. Urges to smoke have also been reported as significant predictors of abstinence in non‐pregnant smokers 37, 40, 41 but have not been assessed in a study of long‐term cessation in pregnancy. Thus, this study examined potential cigarette dependence related predictors of smoking cessation at 4 weeks post‐quit and end‐of‐pregnancy in a rigorously conducted large trial of a smoking cessation intervention during pregnancy among women who attempted to quit.…”
Section: Introductionmentioning
confidence: 99%
“…Despite several FDA approved treatments, the majority of smokers who attempt to quit will ultimately relapse and return to regular smoking behavior within the first year following a quit attempt (Hughes et al, 2004;Wileyto et al, 2004;Jorenby et al, 2006). Numerous risk factors for relapse have been identified (e.g., see Garvey et al, 1992;Doherty et al, 1995;Shiffman et al, 1996b;Ockene et al, 2000;Piasecki et al, 2000;Piasecki et al, 2003), and developing treatments to effectively target these many factors remain a high research priority. In early abstinence, one of the most reliable predictors of relapse is the occurrence a single smoking lapse, which is generally defined as smoking at least a puff of a cigarette (Marlatt and George 1984;Brandon et al, 1990;Kenford et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Three types of evidence directly link both craving and failure to regulate it to drug-taking behavior. First, across substance-using populations, prospective studies show that craving predicts relapse to drug taking following abstinence (9)(10)(11)(12)(13)(14)(15). Second, cognitive-behavioral therapies (CBT) include training in the cognitive regulation of craving, and are effective for treating SUDs (16).…”
mentioning
confidence: 99%